Identification of master regulator genes of UV response and their implications for skin carcinogenesis. (19th November 2018) - Shen, Yao; Chan, Gabriel; Xie, Michael; Zeng, Wangyong; Liu, Liang
Abstract: Solar UV radiation is a major environmental risk factor for skin cancer. Despite decades of robust and meritorious investigation, our understanding of the mechanisms underlying UV-induced skin carcinogenesis remain incomplete. We previously performed comprehensive transcriptomic profiling in human keratinocytes following exposure to different UV radiation conditions to generate UV-specific gene expression signatures. In this study, we utilized Virtual Inference of Protein Activity by Enriched Regulon (VIPER), a robust systems biology tool, on UV-specific skin cell gene signatures to identify master regulators (MRs) of UV-induced transcriptomic changes. We identified multiple prominent candidate UV MRs, including forkhead box M1 (FOXM1), thyroid hormone receptor interactor 13 and DNA isomerase II alpha, which play important roles in cell cycle regulation and genome stability. MR protein activity was either activated or suppressed by UV in normal keratinocytes. Intriguingly, many of the UV-suppressed MRs were activated in human skin squamous cell carcinomas (SCCs), highlighting their importance in skin cancer development. We further demonstrated that selective inhibition of FOXM1, whose activity was elevated in SCC cells, was detrimental to SCC cell survival. Taken together, our study uncovered novel UV MRs that can be explored as new therapeutic targets for future skin cancer treatment. Abstract : We utilized robust systems biology tools to interrogate UV-specific gene expression signatures to identify prominent UV MRs. Our computational, experimental and clinical studies confirmed that FOXM1, a top-ranked MR, is closely involved with skin tumorigenesis.